Effect of preoperative biliary drainage on cholestasis-associated inflammatory and fibrotic gene signatures in perihilar cholangiocarcinoma. Issue 1 (5th November 2018) - Reiniers, M J; de Haan, L; Weijer, R; Wiggers, J K; Jongejan, A; Moerland, P D; Alles, L K; van Kampen, A H C; van Gulik, T M; Heger, M; van Golen, R F
Graphical Abstract: Preoperative biliary drainage (PBD) is used routinely in the evaluation of patients with potentially resectable perihilar cholangiocarcinoma to relieve cholestasis and improve the liver's resilience to surgery. Little preclinical or translatational data are, however, currently available to guide the use of PBD in this patient group. The effect of PBD on hepatic gene expression profiles was therefore studied by microarray analysis. Drainage affects inflammatory and fibrotic gene signatures